Problem-based learning enhanced by electronic textbooks: The effects on students' critical thinking abilities - Ermiana, Ida; Fauzi, Asri; Erfan, Muhammad; Husniati Husniati; Gunawan Gunawan (Universitas Negeri Yogyakarta, 2025)
Students’ critical thinking skills remain relatively low due to learning activities that are still dominated by teacher-centered approaches and the limited use of interactive learning media. This condition makes students less engaged in analyzing, reasoning, and solving problems in a deep and meaningful way. To overcome this issue, the problem-based learning model assisted by electronic textbooks was applied to promote independent, active, and contextual learning. This study aimed to investigate the impact of the PBL model, supported by electronic textbooks, on students’ critical thinking skills. The research employed a quasi-experimental design with a population of 270 students, from which 60 were selected using the cluster random sampling technique. The instrument used was a critical thinking test administered during the pretest and posttest. The data were analyzed using a parametric statistical test, specifically the independent sample t-test. The results showed that the t-value (2.656) was greater than the t-table value (1.671), indicating a significant effect of PBL assisted by electronic textbooks on students’ critical thinking skills. Future research is recommended to explore other innovative learning models, integrate additional learning variables, and apply these models to larger and more diverse samples across various educational levels to obtain more comprehensive and generalizable results.